2018
DOI: 10.3390/socsci7090151
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Identity as a Barrier to Widening Access in Scottish Universities

Abstract: Widening access policy has historically focused on tackling the socioeconomic barriers to university access faced by prospective students from under-represented groups, but increasingly policy makers are seeking to also address the barriers to wider access posed by undergraduate admissions policies. In this vein, the Scottish Government has recently called upon universities to set separate academic entry requirements for socioeconomically disadvantaged applicants which recognise that "the school attainment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…They are, by definition, individuals whose circumstances have prevented them from having as advanced and as deep and developed an education as more traditional students. Some Scottish universities, especially higher tariff ones, have expressed ambivalence about supporting students who might not be ready to hit the ground running (Boliver, Powell and Moreira, 2018). However, there is much good practice across the sector on which to draw, not least within lower tariff universities, which have long supported contextually disadvantaged students to succeed at degree level.…”
Section: Contextualising Prior Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…They are, by definition, individuals whose circumstances have prevented them from having as advanced and as deep and developed an education as more traditional students. Some Scottish universities, especially higher tariff ones, have expressed ambivalence about supporting students who might not be ready to hit the ground running (Boliver, Powell and Moreira, 2018). However, there is much good practice across the sector on which to draw, not least within lower tariff universities, which have long supported contextually disadvantaged students to succeed at degree level.…”
Section: Contextualising Prior Achievementmentioning
confidence: 99%
“…4 The wider project involved interviews with admissions personnel working at Scottish universities, coupled with an analysis of statistical data relating to the educational achievements and trajectories young people in Scotland. The key findings of the interview research are reported elsewhere (Boliver, Powell and Moreira 2018). In this article we focus on the evidence generated by the statistical component of the project.…”
Section: Introductionmentioning
confidence: 99%
“…While rhetoric might prioritise the pursuit of absolute improvements in terms of social mobility, the individualised discourse that is a particular feature of recent policy, but which has its roots in the 1960s, allows the problems caused by wider inequalities to be marginalised. This discourse allows ‘elite institutions’ to recruit the ‘heroic disadvantaged’ (Boliver, Powell, & Moreira, ) without dramatically altering their enrolment strategies or challenging the positions of the already privileged.…”
Section: Discussionmentioning
confidence: 99%
“…This is key for retaining students to graduation (Tinto 1987). However, some interviewees viewed interactions with staff at Durham University as either infrequent or negative, an experience that perhaps reflects the emphasis that self-defining elite universities place on being 'research-intensive' rather than 'teachingfocused' (Boliver, Powell et al 2018).…”
Section: Interactions With Staffmentioning
confidence: 99%
“…First and foremost, universities need to recognise that they may be perpetuating ideas of elitism and forms of 'university culture' that make some students feel excluded. Some highly selective universities -including in the past, Durham -have traded on their self-defined elite status in order to attract students (Boliver, Powell et al 2018). This risks an institution becoming popularly perceived not as 'elite' but rather elitist, 'traditional' and highstatus, and therefore primarily attracting students who associate themselves with these same values.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%